22. THE ARISING OF CRYPTOMARKET: STUDI KASUS SITUS SILK ROAD TAHUN 2011-2015 - Rahmah Rahmah; Ika Riswanti Putranti; Satwika Paramasatya (Journal of International Relations Diponegoro, 2016)
The development of international crimes related to drug trafficking, facilitated by Silk Roadsite since 2011, has thrived on the latest advanced technology. The site has been known as“cryptomarket” introduced by James Martin on his research results in 2013, which were alsoin the spotlight because of the closure of the site in the Silk Road at the same year. AlthoughSilk Road also sales goods other than the categories of drugs, this research proves that untilthe year of 2015, the third version of this site is still focused on the provision of drugs andstill continues to increase from the previous versions. The result of this research represent thedevelopment of cryptomarket through the growth of Silk Road in the years 2011-2015. Thisresearch analyzes the development of the international regime on cybercrime and drugrelatedcrimes, and also compare the development of cryptomarket through Silk Road.